Implementation of Government Budget In the Form of Interest Subsidies for UMKM Sustainability During the Covid-19 Pandemic - Indah Putriyanti; Haliah Haliah; Andi Kusumawati (Lembaga Riset Ilmiah, 2024)
This study aims to determine the government's policy in strengthening UMKM during the Covid-19 pandemic in Indonesia. The research method used in writing this article is the literature review method from various sources related to the Implementation of the government budget in the form of interest subsidies for the sustainability of UMKM during the Covid-19 pandemic. Through the analysis of relevant documents and literature, the results of the study show that this is done by the government in strengthening the sustainability of UMKM, the government provides facilities for delaying principal installments and interest subsidies for micro and small business loans, the government also implements a credit program known as the People's Business Credit (KUR) for UMKM actors. The government is making these efforts to save the sustainability of UMKM. One of the obstacles faced by micro businesses is none other than limited access to capital as the main obstacle for micro and small businesses to develop. To overcome the weaknesses faced by UMKM, various efforts have been made.